The optimum layer number of multi-layer pyramidal core sandwich columns under in-plane compression. Issue 2 (March 2016) - Feng, Li-Jia; Wu, Lin-Zhi; Yu, Guo-Cai
Abstract: The effect of the face thickness to core height ratio on different multi-layer pyramidal core sandwich columns under in-plane compression is investigated theoretically and numerically. Numerical simulation is in good agreement with theory. Results indicate that one specified face thickness to core height ratio corresponds to one optimum layer number of multi-layer pyramidal core sandwich columns in consideration of engineering application. This result can guide the sandwich structure design. Highlights: The effect of layer number on the in-plane compressive property of columns is investigated. The analytical calculations agree well with the simulations. One facesheet-thickness to core-height ratio corresponds to one optimum layer number.